Learn Modesty from Javanese Game - Nathasia Austin Wijaya; Erdhi Widyarto (Soegijapranata Catholic University, 2015)
Todays society, especially for the youth, they have been missed the essence of modesty. The lost of modesty conduce to the lost of modest lifestyle and it is replaced by glamorous lifestyle. It will lead to the careless personality among humans and nature, or even the loss of humanity.The situation can not be ignored and has to be addressed immediately. Therefore, beside the common education, government also implemented character education system in school. Parents have to directing and instantiate their children about modesty and other values. Directing the children can be done with introduce them to Indonesia native culture through Mahesa Jenar Game. Mahesa Jenar is a fictional figure created by S.H. Mintardjas. Mahesa Jenar teaches about modesty, compassion, honesty, justice and wisdom. Mahesa Jenar Game is using RPG as the genre, the outstanding storyline and the interesting animation, makes it suitable for delivering the moral messages.If the children are aware about those values early, hoped those values will help children to develop their character latter on. Keywords education, modesty, interesting, knowledge-based game, lesson, game, mobile game